BASIC LAWS OF DISTRIBUTION AND GENESIS OF PSAMMOPHILOUS COLEOPTERA OF PONTO-CASPIAN REGION IN THE CASE OF TENEBRIONIDAE AND SCARABAEOIDEA (INSECTA: COLEOPTERA) - M. V. Nabozhenko; I. V. Shokhin; G. M. Abdurahmanov; A. M. Klicheva; A. V. Morakhonich; D. I. Oleinik (Юг России: экология, развитие)
The paper deal with migration ways of psammophilous Tenebrionidae and Scarabaeoidea of Ponto-Caspian region since the Pliocene. Reconstruction of genesis of the fauna is made after analyses of contemporary distribution. Zoogeographical analyses of fauna showed the share of species with different distribution in 3 zoogeographical big regions and bassins of Caspian sea, Sea of Azov and Black sea.